Melatih Kecerdasan Emosi Anak Usia Dini - Rika Sa’diyah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2013)
Abstract: Intelligence should be taught to children as early as possible. The importance of emotional intelligence to teach children to provide better opportunities for them in order to exploit their potential. Not a smart little kid academically failing in social life and others. That is, there are other factors beyond the intellect that support children’s success in life. Intellectual and nonintellectual intelligence equally important role in supporting the success of individuals, non-intellectual abilities is essential to predict the ability of individuals to achieve success in life. IQ and EQ capabilities are equally important and mutually supportive, although both have different ways of working. Of the expected ability is not one of them but the balance between the two. Intelligence that enables humans to think rational, logical, and consistent intellectual named. Meanwhile, another intelligence that enables human associative thinking, which is formed by habit and the ability to recognize emotional patterns, called emotional intelligence. Many children experiencing barriers to learning due to the factors of non-intellectual and all that man does is controlled by emotion. Keywords : Intelligence, Emotion, Emotional Intelligence, AUD